Neuropsychological study on the effects of boxing upon athletes' memory - Teng, Y.; Yu, Q.; Yu, X.; Zhan, L.; Wang, K. (The Journal of Strength and Conditioning Research, 2022)
This study attempts to explore the impairment of athletes' memory caused by 1 year of boxing training according to the n-back test and Chinese auditory learning test (CALT). Accordingly, 58 new athletes were prospectively analyzed from a sports school, where 28 athletes who received boxing training were regarded as the exposed group and 30 athletes who received matched training were taken as unexposed group for a duration of 1 year. All subjects respectively completed an n-back test (to test working memory) and a CALT test (to test short-term memory and long-term memory) before and after the training. During the tests, accuracy and reaction time from the n-back test and the correct number from CALT were recorded. The accuracy of the boxing group was observed to be lower than that of the matched group in the 2-back test (p < 0.05), whereas the reaction time of the boxing group was longer than that of the matched group (p < 0.05) after a year of boxing practice. The results of CALT1 (short-term memory), CALT8 (long-term memory), and CALT9 (recognition memory) were lower in the boxing group than that in the matched group after a year (p < 0.05). The results suggest that exposure to 1 year of boxing training can impair the boxers' working memory, short-term memory, and long-term memory. Therefore, boxers should strengthen their head protection during training to avoid frequent impacts to the head.